2024
DOI: 10.11591/edulearn.v18i2.21184
|View full text |Cite
|
Sign up to set email alerts
|

Preservice mathematics teacher knowledge of higher order thinking skills

Juliana Mehelina Herlince Nenohai,
Damianus Dao Samo,
Siprianus Suban Garak
et al.

Abstract: This study aims to describe preservice mathematics teacher knowledge of higher order thinking skills in terms of definition, Bloom's taxonomy level, curriculum, learning, and evaluation. This research is quantitative research with a survey method. and sample consisted of 248 preservice mathematics teachers in semesters VI - VIII of the Department of Mathematics Education, Nusa Cendana University, Timor University, and Wira Wacana Sumba University. The instrument used was a questionnaire about high order thinki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…Research (Lusiana, 2017) shows that the variety of solution methods by students for contextual-based linear equation system problems can overcome problems with different approaches. Nenohai, et al (2024) confirmed that students with good mathematical performance showed problem understanding, planning, implementation, and accurate solutions according to the context. Research by Ratuanik et al (2021) showed that the Indonesian Realistic Mathematics Learning (PMRI) approach improved students' understanding, while Sabil & Winarni (2013) and Sari & Noviartati (2017) highlighted the improvement of students' abilities through the application of PMRI.…”
mentioning
confidence: 63%
“…Research (Lusiana, 2017) shows that the variety of solution methods by students for contextual-based linear equation system problems can overcome problems with different approaches. Nenohai, et al (2024) confirmed that students with good mathematical performance showed problem understanding, planning, implementation, and accurate solutions according to the context. Research by Ratuanik et al (2021) showed that the Indonesian Realistic Mathematics Learning (PMRI) approach improved students' understanding, while Sabil & Winarni (2013) and Sari & Noviartati (2017) highlighted the improvement of students' abilities through the application of PMRI.…”
mentioning
confidence: 63%